(untitled) (EAAE Annual Conference Proceedings, 2019)
Decolonising the curriculum demands curricula and pedagogic change across all academic disciplines. Whereas the contents of architecture may well be epistemologically diverse, the recognized producers of architecture are determinedly less diverse resulting in calls to reconsider who gets to determine what architecture contains. To challenge this, a broader body of knowledge inclusive of gender, class and race is needed, one that responds to both nascent change and persistent instability, and yet remains ‘’live’ — able to adapt to new authors and new audiences as they arise. To generate this knowledge, how we capture and collect it needs to be reimagined too, and the neutral normative, westernized and gendered ideologies and values that persist within architecture’s canon, directly confronted. As both the #BlackLivesMatter and #MeToo movement has demonstrated, social media has provided a rapid response platform through which knowledge is created, communicated and contested. This presentation critically reflects upon the problems and possibilities underpinning three, social-media situated initiatives that sought to repatriate women’s contribution to the canon of architecture. It describes, (1) the production of a crowd-authored list of women architecture writers (2) crowd-sourcing an alternative list of women architects eligible for the #RIBAgoldmedal by Part W and, (3) a crowd-funded, ‘women architects of the world’ Top Trump card game.